1999
DOI: 10.1103/physrevd.60.104054
|View full text |Cite
|
Sign up to set email alerts
|

Gauge invariance of general relativistic tidal heating

Abstract: When a self-gravitating body (e.g., a neutron star or black hole) interacts with an external tidal field (e.g., that of a binary companion), the interaction can do work on the body, changing its massenergy. The details of this "tidal heating" are analyzed using the Landau-Lifshitz pseudotensor and the local asymptotic rest frame of the body. It is shown that the work done on the body is gaugeinvariant, while the body-tidal-field interaction energy contained within the body's local asymptotic rest frame is gaug… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
69
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(70 citation statements)
references
References 17 publications
1
69
0
Order By: Relevance
“…(10.8) and (10.9). Assuming the form of the metric used in the pseudotensorial calculations, for the tidal work they recovered the gauge invariant expressions obtained in [432, 185]. In these approximate calculations the precise form of the boundary conditions (or reference configurations) is not essential, because the results obtained by using different boundary conditions deviate from each other only in higher order.…”
Section: Applications In General Relativitymentioning
confidence: 74%
See 2 more Smart Citations
“…(10.8) and (10.9). Assuming the form of the metric used in the pseudotensorial calculations, for the tidal work they recovered the gauge invariant expressions obtained in [432, 185]. In these approximate calculations the precise form of the boundary conditions (or reference configurations) is not essential, because the results obtained by using different boundary conditions deviate from each other only in higher order.…”
Section: Applications In General Relativitymentioning
confidence: 74%
“…However, gravitational energy (both in Newtonian theory and in general relativity) is only ambiguously defined (and hence, cannot be localized), while the phenomena mentioned above cannot depend on the mathematics that we use to describe them. The first investigations intended to calculate the tidal work (or heating) of a compact massive body were based on the use of various gravitational pseudotensors [432, 185]. It has been shown that, although in the given (slow motion and isolated body) approximation the interaction energy between the body and its companion is ambiguous, the tidal work that the companion does on the body via the tidal forces is not.…”
Section: Applications In General Relativitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, gravitational energy (both in Newtonian theory and in general relativity) is only ambiguously defined (and hence cannot be localized), while the phenomena mentioned above cannot depend on the mathematics that we use to describe them. The first investigations intended to calculate the tidal work (or heating) of a compact massive body were based on the use of the various gravitational pseudotensors [318, 136]. It has been shown that although in the given (slow motion and isolated body) approximation the interaction energy between the body and its companion is ambiguous, the tidal work that the companion does on the body via the tidal forces is not.…”
Section: Applications In General Relativitymentioning
confidence: 99%
“…V. The energy conservation method is simpler to use than the method of integration of the See Refs. [65][66][67][68] for further discussion of the derivation method and of similar tidal work formulas.…”
Section: Effect Of Current Quadrupole On Orbital Motionmentioning
confidence: 99%